2017
DOI: 10.1155/2017/8412093
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Security Application of a Ten-Term Chaotic System without Equilibrium

Abstract: A system without equilibrium has been proposed in this work. Although there is an absence of equilibrium points, the system displays chaos, which has been confirmed by phase portraits and Lyapunov exponents. The system is realized on an electronic card, which exhibits chaotic signals. Furthermore, chaotic property of the system is applied in multimedia security such as image encryption and sound steganography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Compared with chaos, hyperchaos possesses more randomness, complex dynamical behavior, and unpredictability with at least two positive Lyapunov exponents (LEs). Numerous examples of novel hyperchaotic systems [4][5][6][7][8][9] can be intensively discovered, and they have been widely applied in many fields, such as cryptography [10], neural network [11], synchronization [12,13], and secure communications [14,15]. e memristor that had been postulated as the fourth basic circuit element in 1971 by Chua [16] is a two-terminal passive electronic element described by nonlinear constitutive relation of charge q and flux φ and was for the first time fabricated in 2008 by Williams's group of HP Labs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with chaos, hyperchaos possesses more randomness, complex dynamical behavior, and unpredictability with at least two positive Lyapunov exponents (LEs). Numerous examples of novel hyperchaotic systems [4][5][6][7][8][9] can be intensively discovered, and they have been widely applied in many fields, such as cryptography [10], neural network [11], synchronization [12,13], and secure communications [14,15]. e memristor that had been postulated as the fourth basic circuit element in 1971 by Chua [16] is a two-terminal passive electronic element described by nonlinear constitutive relation of charge q and flux φ and was for the first time fabricated in 2008 by Williams's group of HP Labs [17].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of hidden attractor are different from that of self-excited chaotic attractor [28,29]. It has been shown that the dynamical systems having hidden attractors include these systems without equilibrium, with no unstable equilibrium, with one stable equilibrium, and with lines, curves, planes, and surfaces of equilibria [30][31][32][33][34][35]. Recently, perpetual points were introduced as another structural feature of nonlinear systems [36].…”
Section: Introductionmentioning
confidence: 99%